L’évolution des dépenses et recettes des administrations publiques. La poursuite du scénario actuel est-elle possible? - Vézina, Jean-P. (L'Actualité économique, 1977)
AbstractThe importance of the governmental sector increased at a particularly high rate. This has been made possible by higher taxes, especially taxes on personal income. Those taxes increased at an average annual rate of 18% since 1965. One may question on the possibility of increasing again taxes without deteriorating the general performance of the economy. In other words, is it possible to maintain in the future the present scenario, that is to increase the relative importance of the public sector without this being detrimental to the other sectors of the economy? In this article, the author tries to answer these questions.